Ed.D. in Educational Leadership Student Handbook
This handbook will acquaint students with the procedures of the Ed. D. in Educational Leadership Program, with selected policies and regulations of California State University Channel Islands, and with some of the resources available to doctoral students. Students are encouraged to work closely with the Program's Director and other program staff and faculty to complete the degree requirements described in this handbook.